2020
DOI: 10.3390/polym12020413
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Coefficients of Linear Thermal Expansion of Colorless and Transparent Semi-Alicyclic Polyimide Films via Incorporation of Rigid-Rod Amide Moiety: Preparation and Properties

Abstract: Semi-alicyclic colorless and transparent polyimide (CPI) films usually suffer from the high linear coefficients of thermal expansion (CTEs) due to the intrinsic thermo-sensitive alicyclic segments in the polymers. A series of semi-alicyclic CPI films containing rigid-rod amide moieties were successfully prepared in the current work in order to reduce the CTEs of the CPI films while maintaining their original optical transparency and solution-processability. For this purpose, two alicyclic dianhydrides, hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
0
22
1
Order By: Relevance
“…PI‐a and PI‐b films exhibited the CTE values of 63.3 × 10 −6 and 66.7 × 10 −6 /K in the temperature range of 50–200°C, respectively, which were comparable with those of the PI‐ref‐a (CTE = 61.2 × 10 −6 /K) and PI‐ref‐b (CTE = 68.5 × 10 −6 /K). This high‐CTE feature is usually common for the semi‐alicyclic PI films due to the relatively poor intra‐ and intermolecular interactions, which could be remedied by introduction of rigid‐rod units in the diamine moiety or incorporation of inorganic nanoparticles 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI‐a and PI‐b films exhibited the CTE values of 63.3 × 10 −6 and 66.7 × 10 −6 /K in the temperature range of 50–200°C, respectively, which were comparable with those of the PI‐ref‐a (CTE = 61.2 × 10 −6 /K) and PI‐ref‐b (CTE = 68.5 × 10 −6 /K). This high‐CTE feature is usually common for the semi‐alicyclic PI films due to the relatively poor intra‐ and intermolecular interactions, which could be remedied by introduction of rigid‐rod units in the diamine moiety or incorporation of inorganic nanoparticles 19 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the research hot‐topics for semi‐alicyclic CPI films have mainly been focused on the modification of their CTE and flame retardancy. There have been many reports on the enhancement of high‐temperature dimensional stability of semi‐alicyclic CPI films; that is the reducing of the CTE values of the films in the literature 19‐21 . However, to the best of our knowledge, there are few reports on the enhancement of flame retardancy of the semi‐alicyclic CPI films.…”
Section: Introductionmentioning
confidence: 99%
“…The microscop phologies of the PI NFMs were investigated by SEM measurements and the re A series of PI (HTDA-BDAF) NFMs were fabricated by the electrospinning procedure, as shown in Figure 5, with the tailored solid contents of the starting PI solution and the electrospinning parameters shown in Table 1. In order to understand the effects of the molecular structure on the properties of the PIs, the PI (HTDA-BDAF) film was also prepared with a procedure according to our previous work [30]. The appearances of the free-standing PI film and NFM are shown in Figure 6a,b, respectively.…”
Section: Pi Resin Synthesis and Electrospun Pi Nfm Preparationmentioning
confidence: 99%
“…36 Generally, PIs with the highly rigid main chains possess the low CTE values due to the large packing density. 30,37 Moreover, the low CTE values of PIs are also dominated by the degree of molecular in-plane orientation. 38,39 Here, the introduction of cyclohexyl and methyl groups into PIs enhanced their molecular mobility and resulted in the relatively high CTE values.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…[23][24][25][26][27] However, the approaches to enhance transparency or solubility of PIs are usually contradicted with the demand to keep their good inherent properties, such as excellent mechanical properties, thermal stability and so on. [28][29][30] Fortunately, it is considered an effective way that incorporating bulky pendant groups into PIs to improve their processability and transparency, and meanwhile maintain their high thermal stability. [31][32][33][34] In previous work, we found that the introduction of cyclohexyl and tert-butyl groups into PIs was able to increase their T g s, solubility and transparency, 34 but the cost was relatively high.…”
Section: Introductionmentioning
confidence: 99%